The space in-between - Candiotto, Laura (My University, 2022)
The first set of topics is dedicated to the theoretical framework I employ in my target article. I will explain (a) why sense-making is participatory from the beginning and (b) how a personal communication with a place is possible. The second set of topics tackles my proposal’s ethical and political significance. I will consider (c) the objection on how it is possible to love the unlovable and (d) the question of what should change for us to love nature.
Meziprostor
Keywords: native; nature; place; love; rodný; příroda; místo; láska